An analysis of students' knowledge and choice criteria in retail bank selection in sub-Saharan Africa: The case of Ghana - Narteh, B.; Owusu-Frimpong, N. (International Journal of Bank Marketing, 2011)
Purpose: This study aims to offers a deeper insight into bank selection of Ghanaian students so as to offer bank managers the opportunity to tailor-measure programmes aimed at attracting and retaining customers. Design/methodology/approach: The study employed both qualitative and quantitative methods to investigate the problem. The "drop and pick" convenience sampling method adopted resulted in 223 completed questionnaires. The mean ranking and factor analysis methods were employed to identify the major factors that influence the respondent bank selection. Findings: Over all, student customers consider image, attitude and behaviour of staff, core service delivery and technology-related factors as the major issues that influence consumers' decision to open and maintain an account. Research limitations/implications: The limitation of the study relates to the student population used for the study, which limits the generalisability of the findings. The study, however, contributes to the academic knowledge of bank selection and provides insights into the critical factors considered by sample students in their bank selection decisions. Practical implications: In a market where consumers respond differently to a marketing offer, market segmentation becomes a necessity and therefore differences in male and female consumers' selection criteria emanating from this study provide an excellent opportunity for the banks to adopt segmentation-based strategies to serve the customers. Originality/value: In this paper, gender and educational level provide a deeper understanding of bank selection criteria among the Ghanaian bank customers. The four constructs can be used by bank management as bases for designing marketing strategies to deliver efficient service, and engage in relationship marketing practices to attract and retain customers. © Emerald Group Publishing Limited.
Keywords: Attitudes; Bank selection; Customer services quality; Front line staff; Ghana; Image of bank; Technology